Synthesis and biological characterisation of novel N-alkyl-deoxynojirimycin alpha-glucosidase inhibitors. - Rawlings, A; Lomas, H; Pilling, A; Lee, M; Alonzi, D; Rountree, J; Jenkinson, S; Fleet, G; Dwek, R; Jones, J; Butters, T (2009)
The N-alkylated deoxynojirimycin compound, N-(6'-(4''-azido-2''-nitrophenylamino)hexyl)-1-deoxynojirimycin (6) was synthesised as a potential photoaffinity probe for endoplasmic reticulum (ER) alpha-glucosidases I and II. Surprisingly this compound was a highly potent inhibitor of alpha-glucosidase I (IC(50), 17 nM) in an in vitro assay and proved equally effective at inhibiting cellular ER glucosidases, as determined by a free oligosaccharide (FOS) analysis. A modest library of compounds was synthesised to obtain structure-activity information by variation of the N-alkyl chain length and modifications to the azido-nitrophenyl group. All of these compounds failed to improve on the efficacy of compound 6, but most showed greater enzyme inhibitory potency than N-butyl-deoxynojirimycin (NB-DNJ), a pharmacological agent that has been evaluated for the treatment of several viruses for which infectivity is dependent on host cell glycosylation.